Navigating Intermedial Adaptation Through Translation: Dear Shameless Death Dirmit - Sağlam, Naciye (Palgrave Macmillan, 2025)
This chapter investigates the intermedial adaptation of Latife Tekin’s novel Sevgili Arsız Ölüm (Dear Shameless Death) into the stage performance Sevgili Arsız Ölüm Dirmit (Dear Shameless Death Dirmit), framing it as a translation practice. Translation being a practice that extends beyond language today makes it applicable to multimodal contexts and closely aligns with adaptation. Engaging with key theories in adaptation, intermediality and translation, the chapter argues that translating a novel into a stage performance constitutes a dynamic re-creation in which visual, auditory, and spatial elements converge to generate meaning on stage. By analyzing narrative structure, stage design, and language, the chapter explores how Tekin’s storytelling is reinterpreted for the stage, proposing the concept of coherence in difference. Conclusively, it enhances our understanding of the complex relationship between novel and stage, challenging conventional notions of adaptation and translation as mere derivatives while advocating for appreciation of multimodal translation practices. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.
Keywords: Coherence in difference; Intermediality; Multimodality; Stage adaptation; Translation